Note: a laser-flash photolysis and laser-induced fluorescence detection technique for measuring total HO2 reactivity in ambient air - Miyazaki, K; Nakashima, Y; Schoemaecker, C; Fittschen, C; Kajii, Y (Review of scientific instruments, 2013)
A novel instrument for measuring total HO2 reactivity in the troposphere was successfully developed using a laser-flash photolysis and laser-induced fluorescence detection technique. Validation and testing were conducted through kinetic measurements of the reaction of HO2 radicals with NO2, and the results were found to be in good agreement with recent recommended values. The limit of detection (LOD) for HO2 loss rate measurement is achieved to be 0.024 s(-1) (3σ) with 60 times decay integrations. An observation of ambient air was carried out in a suburb of Tokyo to test the practical use of the developed instrument and un-expected rapid HO2 loss rate has been observed.